63 Impact of an Orthogeriatric Service on Osteoporosis Management in HIP Fracture Patients. (20th December 2019) - Amini, Homaira; Ong, Kevin; Strivens, Edward
Abstract: Background: Osteoporosis which is now treatable is the major risk factor for hip fractures in the elderly. Having a hip fracture increases morbidity and mortality. Hip fractures are costly. Incidence increases with age. Aims: To examine how introduction of an orthogeriatric service (OGS) improves osteoporosis management. Method: A dedicated OGS was established in the orthopaedic unit in an Australian tertiary teaching hospital in July 2014. Retrospective analyses were undertaken to compare osteoporosis diagnosis and treatment rates in patients ≥ 65 years old presenting with minimal trauma hip fractures (MTHF) before and after the OGS was established. Results: 1. 108 MTHF (mean age 81 years) and 107 MTHF (mean age 82 years) were admitted in 2014 respectively before and after the OGS was established. 2. New osteoporosis diagnoses increased by 27%, new calcium &/or vitamin D prescription increased by 17% and new antiresorptive treatment increased by 30%, after the OGS was established. 3. The odds ratio for receiving a new diagnosis of osteoporosis post MTHF with the OGS compared to pre-OGS was 4.4 (2.1 – 9.0), p<0.0001. 4. The odds ratio for initiating new antiresorptive treatment post fractured NOF with OGS compared to pre-OGS was 6.2 (3.0 – 12.7), p<0.0001. 5. Rates of new diagnoses of osteoporosis and initiation of antiresorptive treatments with the OGS were not affected by age or gender. Conclusion: 1. Introduction of a dedicated OGS improved osteoporosis diagnoses and initiation of antiresorptive treatments. 2. Patients who received a new diagnosis of osteoporosis and/or started on antiresorptive treatment were also likely to be prescribed calcium and/or vitamin D supplements as well. 3. There did not appear to be any age or gender bias towards giving more new diagnoses of osteoporosis and/or more new antiresorptive treatments with a dedicated OGS. 4. These results may be useful for benchmarking and comparison purposes.